Clinical Outcomes of Crizotinib Readministration in Patients with Nonsmall Cell Lung Cancer with Anaplastic Lymphoma Kinase Rearrangement: Case Report and Review of Literature - Parida, Prasant Kumar (Indian Journal of Medical and Paediatric Oncology, 2023)
Recent studies have demonstrated promising outcomes of the first-line anaplastic lymphoma kinase-tyrosine kinase inhibitor (ALK-TKI) “crizotinib” in patients with locally advanced and metastatic lung cancers with high expression of the fusion protein “EML4-ALK.” High drug resistance, however, restricts the therapeutic advantages of ALK-TKIs in patients with nonsmall cell lung cancer (NSCLC). The contemporary literature documents limited treatment approaches for patients with NSCLC relapse or nonresponsiveness to second-/third-generation ALK-TKIs. We hereby provide a descriptive analysis of five NSCLC cases treated with crizotinib, ceritinib, and alectinib for a median duration of 54 months. The outcomes indicate a profound therapeutic response in patients receiving 4th and subsequent line of treatment with crizotinib. The crizotinib retreatment actively reduced patient resistance to the ALK-TKIs by reversing the mesenchymal epithelial transition amplification. The results from this case series also emphasize the possible role of next-generation sequencing in determining therapeutic resistance and transforming the treatment paradigm for NSCLC. Partial response was observed in the patients after 6 months of crizotinib readministration. This is possibly the first case series reporting crizotinib rechallenge in patients of ALK positive NSCLC who failed on subsequent ALK-TKIs and multiple lines of chemotherapies.
Keywords: NSCLC; lung cancer; EML4-ALK; ALKi